Microstructure and Mechanical Properties of AZ31/ZrO2 Composites Prepared by Friction Stir Processing With High Rotation Speed - Zang, Qianhao; Li, Xiaowen; Chen, Hongmei; Zhang, Jing; Wang, Ling; Chen, Shujin; Jin, Yunxue; Lu, Sheng (Frontiers in Materials, 2020)
The Nano-ZrO2 reinforced AZ31 alloy composites were fabricated by friction stir processing (FSP) with three multi-pass and high rotation speed. The AZ31/2.14 vol% ZrO2, AZ31/4.29 vol% ZrO2 and AZ31/6.43 vol% ZrO2 composites were designed. The fine microstructure and uniform dispersion of ZrO2 particles were observed in the AZ31/ZrO2 composites. The excellent interfacial bonding was observed between the Mg matrix and ZrO2. The hardness and tensile properties were enhanced after three cumulative FSP passes. This was attributed to grain refinement and strengthening effects of ZrO2. The tensile properties and hardness of the AZ31/ ZrO2 composite increased with the increase of volume fraction of the ZrO2 particles from 2.14 vol% to 6.43 vol%.